2007
DOI: 10.4103/0019-5278.34532
|View full text |Cite
|
Sign up to set email alerts
|

Visual functions of commercial drivers in relation to road accidents in Nigeria

Abstract: Objective:To determine the effects of the visual functions on the occurrence of road traffic accidents (RTA) amongst commercial drivers in Ife central local government area (LGA) of Osun state of Nigeria.Design:A cross-sectional study.Settings:Four major motor parks located at Ife Central LGA.Materials and Methods:Of the estimated 270 commercial drivers in the four major parks of the LGA, 215 consecutive drivers were interviewed and had their eyes examined. Structured questionnaires were administered by an oph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 9 publications
6
35
2
Order By: Relevance
“…Therefore, visual assessment of drivers is a major health issue. The prevalence of visual impairment in this study in the better eye was 2.2% and this finding is close to a Nigerian study by Oladehinde et al which reported prevalence of visual impairment in the better eye of 3.3% [16] . A study carried out by Adekoya et al reported a prevalence of visual impairment of 2.8% in the better eye [17] .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, visual assessment of drivers is a major health issue. The prevalence of visual impairment in this study in the better eye was 2.2% and this finding is close to a Nigerian study by Oladehinde et al which reported prevalence of visual impairment in the better eye of 3.3% [16] . A study carried out by Adekoya et al reported a prevalence of visual impairment of 2.8% in the better eye [17] .…”
Section: Discussionsupporting
confidence: 78%
“…There was no significant association between involvement in RTA and visual impairment in this study (p value = 0.94 and 0.61 respectively). This finding is in contrast with the findings of other studies by Oladehinde et al and Nwosu et al [16,19] . None of the respondents had colour vision abnormality.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies have revealed that majority of drivers in Nigeria had no eye test or formal drivers training before obtaining their driver's license and most of the licenses had been proven to be fake. [ 7 8 9 ] In the Niger Delta areas, these risk factors are worsened by cultism, military assault on civilians, robbery, kidnapping, and militant activities as a result of agitations for crude oil compensation. The challenge of head injury is daunting as the health system is inadequately prepared to address the cause and mitigate the associated health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Drivers with good vision have an advantage over those with poor vision. Refractive error is a commonly reported ocular morbidity among drivers [6-8]. In Africa and generally in Nigeria, drivers do not often go for routine medical or eye examination.…”
Section: Introductionmentioning
confidence: 99%